2013
DOI: 10.1016/j.semcancer.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and competition in the dynamics of tissue architecture during homeostasis and tumorigenesis

Abstract: The construction of a network of cell-to-cell contacts makes it possible to characterize the patterns and spatial organization of tissues. Such networks are highly dynamic, depending on the changes of the tissue architecture caused by cell division, death and migration. Local competitive and cooperative cell-to-cell interactions influence the choices cells make. We review the literature on quantitative data of epithelial tissue topology and present a dynamical network model that can be used to explore the evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…The nearest-neighbors probability distribution qualitatively resembles the organization of cells arising from a cooperators model, with the number of nearest neighbors ranging from three to eight with a maximum at six. 15 This is different from the defector model, typically representing epithelial cancers where the cells tend to adopt a cheating or defective behavior as opposed to cooperation. In a defector model, the cells replicate and differentiate in an uncontrolled way, resulting in a probability distribution more shifted toward higher values, including a small but measurable number of cells having 10 nearest neighbors.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The nearest-neighbors probability distribution qualitatively resembles the organization of cells arising from a cooperators model, with the number of nearest neighbors ranging from three to eight with a maximum at six. 15 This is different from the defector model, typically representing epithelial cancers where the cells tend to adopt a cheating or defective behavior as opposed to cooperation. In a defector model, the cells replicate and differentiate in an uncontrolled way, resulting in a probability distribution more shifted toward higher values, including a small but measurable number of cells having 10 nearest neighbors.…”
Section: Resultsmentioning
confidence: 98%
“…Such analysis has been successfully used for the segmentation of epithelial cancers from healthy tissue in digitized histological images 14 and epithelial organizations across different species and kingdoms of life. 15 Another useful parameter is the average number of Delauney nearest neighbors. It has been shown that in many complex cellular structures, cells are most likely to have six neighbors, 16,17 while in other organization types, they might have four or even nine (tumors, for instance).…”
Section: Introductionmentioning
confidence: 99%
“…While regular lattices neglect the importance of variation in connectivity, scale-free networks are not appropriate if players are distributed on a planar network. The distribution of cells in biological tissues resembles a Voronoi diagram [Lewis 1928, Honda 1978, Gibson & Gibson 2009, Csikász-Nagy et al 2013] rather than a regular lattice or a scale-free network.…”
Section: Voronoi Networkmentioning
confidence: 99%
“…A Voronoi network is defined as a group of such node-joining segments [ Figure 1]. The average connectivity of Voronoi networks is 6, with a unimodal distribution in which fewer than 4 or more than 8 connections are very rare -similar to what is observed in biological samples, both within and among species [Lewis 1928, Gibson & Gibson 2009, Csikász-Nagy et al 2013.…”
Section: Voronoi Networkmentioning
confidence: 99%
See 1 more Smart Citation